2015
DOI: 10.1124/mol.115.100172
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Identification of Novel Positive Allosteric Modulators of the Human Dopamine D2 and D3 Receptor

Abstract: Agonists at dopamine D2 and D3 receptors are important therapeutic agents in the treatment of Parkinson's disease. Compared with the use of agonists, allosteric potentiators offer potential advantages such as temporal, regional, and phasic potentiation of natural signaling, and that of receptor subtype selectivity. We report the identification of a stereoselective interaction of a benzothiazol racemic compound that acts as a positive allosteric modulator (PAM) of the rat and human dopamine D2 and D3 receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 29 publications
5
38
0
Order By: Relevance
“…The antidepressant bupropion is racemic as is its major metabolite hydroxybupropion; however, the (2S, 3S)-hydroxy isomer is significantly more potent than the (2S, 3R)- hydroxy isomer (Damaj et al, 2004). In a recent report investigating novel allosteric modulators of dopamine receptors, which are of interest for the treatment of Parkinson's disease, it was found that the (R)-isomer acted as a positive allosteric modulator, whereas the (S)-isomer had negative allosteric modulator properties (Wood et al, 2016). Examples of enantiomers having synergistic properties have also been reported, including enantiomeric iminosugars (Jenkinson et al, 2011) and methadone (Silverman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The antidepressant bupropion is racemic as is its major metabolite hydroxybupropion; however, the (2S, 3S)-hydroxy isomer is significantly more potent than the (2S, 3R)- hydroxy isomer (Damaj et al, 2004). In a recent report investigating novel allosteric modulators of dopamine receptors, which are of interest for the treatment of Parkinson's disease, it was found that the (R)-isomer acted as a positive allosteric modulator, whereas the (S)-isomer had negative allosteric modulator properties (Wood et al, 2016). Examples of enantiomers having synergistic properties have also been reported, including enantiomeric iminosugars (Jenkinson et al, 2011) and methadone (Silverman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that the indole-2-carboaxamide chemical structure of SB269652 is very similar to a recently identified positive allosteric modulator for D 2 and D 3 receptors, suggesting that understanding the binding mechanism of SB269652 to these receptors could lead to the development of both D 2 and D 3 receptor-specific positive and negative allosteric compounds (Wood et al, 2016).…”
Section: Sb269652 As the Leading Compound That Led To The Developmentmentioning
confidence: 68%
“…Taken together, these results indicate that the 7-CN-THIQ moiety of SB269,652 binds directly to the orthosteric site, while the indole-2-carboxamide portion determines the binding to the second allosteric site. Interestingly, the indole-2-carboxamide part of SB269,652 has a structure similar to another recently discovered positive allosteric modulator for D 2 and D 3 receptors, suggesting the relevance of this second site for developing new allosteric compounds [ 43 ]. Thus, the SB269,652 molecule can be exploited in two different ways, either as a dualsteric compound as it is or eventually as a block from which new allosteric drugs can be generated based on its indole-2-carboxamide moiety.…”
Section: A New Approach To Target Dopamine Receptor Dimers: Bitopic Lmentioning
confidence: 92%